Thermochemolysis of the Murchison meteorite: identification of oxygen bound and occluded units in the organic macromolecule - Watson,JS; Sephton,MA; Gilmour,I (INT J ASTROBIOL, 2010)
An organic macromolecular residue, prepared from the Murchison meteorite by treatment with hydrofluoric and hydrochloric acids, was subjected to online thermochemolysis with tetramethylammonium hydroxide (TMAH). The most abundant compound released by thermochemolysis was benzoic acid. Other abundant compounds include methyl and dimethyl benzoic acids as well as methoxy benzoic acids. Short chain dicarboxylic acids (C4–8) were also released from the organic macromolecule. Within the C1 and C2 benzoic acids all possible structural isomers are present reflecting the abiotic origin of these units. The most abundant isomers include 3,4-dimethylbenzoic acid (DMBA), 3,5-DMBA, 2,6-DMBA and phenylacetic acid. Thermochemolysis also liberates hydrocarbons that are not observed during thermal desorption; these compounds include naphthalene, methylnaphthalenes, biphenyl, methylbiphenyls, acenaphthylene, acenaphthene, phenanthrene, anthracene, fluoranthene and pyrene. The lack of oxygen containing functional groups in these hydrocarbons indicates that they represent non-covalently bound, occluded molecules within the organic framework. This data provides a valuable insight into oxygen bound and physically occluded moieties in the Murchison organic macromolecule and implies a relative order of synthesis or agglomeration for the detected organic constituents.